Study on marketing channel and value chain analysis of some commercially important marine fish species available in Coxs bazar area, Bangladesh - Ahsan, Md Khabirul; Ghosh, Subrata Kumar; Runa, Nusrat Sultana; Hasan, Muhammad Mehedi; Kamal, Md (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to investigate marketing channel and value chain analysis of some commercially important marine fish species available in Coxs Bazar area, Bangladesh. Three commercially important marine fish species were investigated in respect to their marketing channel and value analysis: 1) Pomfret, Stromateus chinensis, 2) Jewfish, Otolithoides argenteus and 3) Hilsha, Tenualosa ilisha. Three marketing channels mainly encompasses from fishermen to consumers, namely the primary, secondary and retail markets involving sales agents, suppliers, wholesalers, commission agents, processors and retailers. A total of 120 fishermen and intermediaries involved in the channels were interviewed. A large number of intermediaries were found to be involved in the marketing channel and this group is believed to make huge profit, thus the prices of fishes were very high in the final consumer market. Marketing margin and profit also analyzed. Marketing margin for Pomfret fish, Jewfish and Hilsha were 21%, 27% and 27% of consumer purchase price, respectively. Poor road and transport facilities and large number of intermediaries in the chain were some of the major problems of marine fish marketing chain. It was therefore necessary to provide organizational support, government support, extension service and training facilities to the market operators for sustainable fish marketing systems. Res. Agric., Livest. Fish.3(1): 195-201, April 2016